Interpretation of Nusyuz According to Hasbi Ash-Shiddiqie in Tafsir An-Nur: Analysis Study of Surah An-Nisa Verse 34 - Ucun Nenah Hopidoh; Muhamad Aroka Fadli; Ikin Sodikin (al-Afkar, Journal For Islamic Studies, 2024)
This research aims to explain how the attitude of a husband towards a nusyuz wife from the perspective of An-Nur's interpretation and to explain how QS is implemented. An-Nisa verse 34 in everyday life. The method used in this research is a qualitative method with a literature study approach that emphasizes the view of the Qur'an. The results of the research show that Islam has regulated the problem of nusyuz of a wife in Al-Qur'an surah An-Nisa verse 34. As for the attitude that a husband should do towards a wife who is nusyuz, it is (1) Giving advice (2) Staying away from his wife (3) Hitting with a rate of blows that does not hurt. If after performing these actions it still does not bring results or does not make the wife return to obeying her husband, then the problem must be submitted to a third party (judge or mediator). As for the implementation of surah An-Nisa verse 34 in everyday life, among them are: A husband must have a spirit of leadership, a wife has the right to receive good treatment from her husband, God will take care of a pious wife, a husband must take care of his wife well, cannot reproach, sneer, or hurt her, a good and wise husband will never hurt or hit his wife in a painful way, and God has warned us with His power and greatness not to cheat and oppress a wife.